新型高效光伏发电聚光装置 (2018)
本发明公开了种新型高效光伏发电聚光装置，包括反射圆筒、第圆形电池片、第二圆形电池片、底座、上反射板和下反射板，所述反射圆筒为圆筒状，其口部直径大于底部直径，在反射圆筒的底部安装第圆形电池片和第二圆形电池片，且第圆形电池片和第二圆形电池片背面靠背面固定连接在起，第二圆形电池片通过伸缩部件与底座连接，在底座的两端对应第二圆形电池片的受光面安装下反射板，底座通过蛇管连接上反射板，上反射板位于下反射板上方，并与下反射板相对应。本发明结构简单，设计合理，容易制造，成本低廉，能充分利用太阳能，并且反射到电池板的光线均匀。 The invention discloses a novel high-efficiency photovoltaic power generation and condensation device. The device comprises a reflection cylinder, a first circular cell, a second circular cell, a pedestal, upper reflecting plates and low reflecting plates; and the reflection cylinder is cylindrical, the diameter of an opening portion of the cylinder is greater than that of the bottom of the cylinder, the first circular cell and the second circular cell are mounted in the bottom of the reflection cylinder and are fixedly connected in a back-to-back manner, the second circular cell is connected to the pedestal via a telescopic part, the two ends of the pedestal are provided with the lower reflecting plates corresponding to a light-receiving surface of the se